2008
DOI: 10.1007/s00270-008-9376-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Symptomatic Vertebral Fractures in Patients After Percutaneous Vertebroplasty

Abstract: The aim of this study was to evaluate the incidence of secondary symptomatic vertebral compression fractures (VCFs) in patients previously treated by percutaneous vertebroplasty (VTP). Three hundred sixteen patients with 486 treated VCFs were included in the study according to the inclusion criteria. Patients were kept in regular follow-up using a standardized questionairre before, 1 day, 7 days, 6 months, and 1 year after, and, further on, on a yearly basis after VTP. The incidence of secondary symptomatic VC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 18 publications
1
23
0
2
Order By: Relevance
“…[9][10][11][12][13]20 On the other hand, some studies have reported an increased risk of new VCFs after PV. 5,6,8,20,21 However, most of these studies were small nonrandomized follow-up only studies, lacking a control group without intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13]20 On the other hand, some studies have reported an increased risk of new VCFs after PV. 5,6,8,20,21 However, most of these studies were small nonrandomized follow-up only studies, lacking a control group without intervention.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Others dispute this assumption and consider the incidence of new VCFs dependent on the presence and severity of osteoporosis. [9][10][11][12][13] To elucidate this controversy, we assessed the incidence of new VCFs during follow-up in 202 patients with acute VCFs randomized to PV and conservative therapy from VERTOS II.…”
mentioning
confidence: 99%
“…However, few patients return to the hospital due to recurrent back pain after PVP. The main discussion is lacking regarding the cause of new compression fracture after PVP; new collapse occur more often in the adjacent vertebral bodies to those treated by PVP [5][6][7] and in the ''sandwich'' bodies levels localized between two somatic collapses [8].…”
Section: Introductionmentioning
confidence: 99%
“…Reported complications, possibly due to the addition of a material that is stiffer than the surrounding bone, include fractures of the augmented and adjacent vertebrae. New osteoporotic vertebral compression fractures, in the months after VP, are reported in 7-63 % of VP patients, up to 82 % of these occur at the adjacent levels, with adjacent fractures occurring sooner than nonadjacent fractures; rates of recurrent fracture of the augmented vertebra itself range up to 63 % in the literature [1,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. It is still under debate whether new vertebral fractures appear more often in patients who received cement augmentation than in conservatively treated patients; some studies support this hypothesis [1,6,7,[27][28][29], while others question it [2,3,26,30].…”
Section: Introductionmentioning
confidence: 99%